Caracterização e solubilização de lodo anaeróbio provenientes de reatores de baixo tempo de retenção celular - Luna, Ysa Helena Diniz Morais de (2017)
The biological sludge approprieate treatment must be developed in order to take advantages of the products generated during the process. However, the anaerobic sludge treatment is arduous due to the complexity of the substances present in sludge flakes, granules and biofilms, becoming indispensable a pre-treatment step in order to raise the solubilization of the materials. At this study, anaerobic sludges produced by anaerobic reactos with low cell retention time (CRT) (2, 4, 6, 8, 10 and 20 days) were characterized and the 2 and 8 day sludge were submitted to solubilization from pre- treatment commonly called alkaline hydrolysis, consisting of the use of NaOH to reach pH 12, and subjected to stirring for 48 hours at room temperature. The objective of this study was to characterize the anaerobic sludges and evaluate the increase of organic materials solubilization, and make comparisons. The results of the soluble organic materials at 2 and 8 days, showed an increase in the concentrations of 14 and 28 times COD, 20 and 40 times to DQOS, 21 and 63 times to carbohydrates and 31 to 60 times to proteins respectively The solubilization of the 8-day solubilized sludge showed higher solubilization than the 2-day sludge, showing that the use of anaerobic low-CRT reactor to generate sludge is interesting in order to produce a sludge that releases higher amounts of soluble materials after a hidrolisis process, be rapidly degradeted by the anaerobic digestion.